PROBABILISTIC FATIGUE LIFE PREDICTION APPROACH FOR MULTI-SITE DAMAGE COMPONENTS - XIE LiYang; MA YuanYuan; LIU JianZhong; WU NingXiang; CHEN Bo (Jixie qiangdu)
Fatigue is a phenomenon of high uncertainty,especially for components with multiple damage sites.The fatigue life（ either mean value or probability distribution of the random variable） of a complex component with multiple damage sites is not equal to that of a simple component with only one damage site.A multi-site damage component is a series system with many weak links（ damage sites） in probability sense.A probabilistic fatigue life prediction model for multi-site damage component is presented based on a systematic thought,as well as the order statistics and extreme statistics concept.Such developed model can naturally reflect the effect of the dependence among different damage sites.Experimental result and the example on multi-site damage component fatigue life prediction shows that the fatigue life of a multi-site damage component is much lower than that of a single site damage component.